Social Stimulus Causes Aberrant Activation of the Medial Prefrontal Cortex in a Mouse Model With Autism-Like Behaviors - Pirone, Antonella; Alexander, Jonathan M.; Koenig, Jenny B.; Cook-Snyder, Denise R.; Palnati, Medha; Wickham, Robert J.; Eden, Lillian; Shrestha, Neha; Reijmers, Leon; Biederer, Thomas; Miczek, Klaus A.; Dulla, Chris G.; et al. (Frontiers in Synaptic Neuroscience, 2018)
Autism spectrum disorder (ASD) is a highly prevalent and genetically heterogeneous brain disorder. Developing effective therapeutic interventions requires knowledge of the brain regions that malfunction and how they malfunction during ASD-relevant behaviors. Our study provides insights into brain regions activated by a novel social stimulus and how the activation pattern differs between mice that display autism-like disabilities and control littermates. Adenomatous polyposis coli (APC) conditional knockout (cKO) mice display reduced social interest, increased repetitive behaviors and dysfunction of the β-catenin pathway, a convergent target of numerous ASD-linked human genes. Here, we exposed the mice to a novel social vs. non-social stimulus and measured neuronal activation by immunostaining for the protein c-Fos. We analyzed three brain regions known to play a role in social behavior. Compared with control littermates, APC cKOs display excessive activation, as evidenced by an increased number of excitatory pyramidal neurons stained for c-Fos in the medial prefrontal cortex (mPFC), selectively in the infralimbic sub-region. In contrast, two other social brain regions, the medial amygdala and piriform cortex show normal levels of neuron activation. Additionally, APC cKOs exhibit increased frequency of miniature excitatory postsynaptic currents (mEPSCs) in layer 5 pyramidal neurons of the infralimbic sub-region. Further, immunostaining is reduced for the inhibitory interneuron markers parvalbumin (PV) and somatostatin (SST) in the APC cKO mPFC. Our findings suggest aberrant excitatory-inhibitory balance and activation patterns. As β-catenin is a core pathway in ASD, we identify the infralimbic sub-region of the mPFC as a critical brain region for autism-relevant social behavior.